Legitimacy of national political elections and implications on foreign direct investment in Zimbabwe’s second republic - Chawatama, R. (BUSE, 2024)
The main purpose of the study was to investigate the implications of legitimacy of national political elections on Foreign Direct Investment (FDI) in Zimbabwe. The methodology was qualitative research, and the research design was a case study. The sample size was fourteen (14), comprising members of different political parties in Zimbabwe; Zimbabwe African National Union Patriotic Front (ZANU-PF) and Citizen for Coalition Change (CCC), Zimbabwe Electoral Commission (ZEC) officials, Ministry of Foreign Affairs and International Trade officials, and officials from the Ministry of Finance, Economic Development and Investment Promotion. Key findings were that illegitimate elections attracts sanctions, political uncertainty, investor uncertainty and political instability thus low FDI. To promote FDI, strategies such as infrastructural development, policy consistency, investment incentives and rule of the law may be implemented. It was concluded that illegitimate elections negatively affects FDI inflows into Zimbabwe. This is because illegitimate elections lead to political instability, investor uncertainty, economic sanctions, and reduced access to international markets. Also, the study made the conclusion that illegitimate elections discourage investment as investors seek stable and predictable environments. Slowed economic growth come due to capital flight, imposed sanctions, political instability which are all products and results of disputed and illegitimate elections. The study recommended that government implements electoral reforms by conducting a comprehensive review of the Electoral Act, align laws with international best practices and engage all stakeholders in the reform process
Keywords: Political elections; Foreign Direct Investment; Zimbabwe